Improving the user experience through practical data analytics gain meaningful insight and increase your bottom line - Fritz, Mike; Berger, Paul D. 1943- (Morgan Kaufmann, 2015)
Improving the User Experience through Practical Data Analytics is your must-have resource for making UX design decisions based on data, rather than hunches. Authors Fritz and Berger help the UX professional recognize and understand the enormous potential of the ever-increasing user data that is often accumulated as a by-product of routine UX tasks, such as conducting usability tests, launching surveys, or reviewing clickstream information. Then, step-by-step, they explain how to utilize both descriptive and predictive statistical techniques to gain meaningful insight with that data. You'll be.
Includes bibliographical references and index. - Print version record
Keywords: Data mining; Quantitative research; Exploration de données (Informatique); Recherche quantitative